MINAT MUZAKKI MEMBAYAR ZAKAT MELALUI LEMBAGA (STUDI KASUS DI PROVINSI BENGKULU) - Asnaini Asnaini (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
This research is about the interest of the community to pay zakat to the institution, what things can motivate the interest of muzakki in zakat to the institution, why they do not choose the zalcat  institution as a means to distrib- ute the zakat,  whereas Shari’ah and  the rules  of the law in Indonesia command the zakat managed by the institution. This study  concludes that  some  people motives in tithe, there is a zakat  to give compensation. Berzakat to keep  the fraternity, avoid  the conversation / slander of others, seek safe, or to remove the doubts / fears of zakatnya not to the rightful. These motives are highly individualized. This motif should not exist in zakah. Based on the motives described, to cultivate the interest of the community to pay zakat to BAZ institutions, can be done, among others: by providing a continuous understanding of the  function, purpose, and  nature of zakat ; providing a truly attractive BAZ institution, able  to accommodate the  needs of muzakki, able  to provide muzakki and  mustahik servants well; and  able  to build an emotional connection between institutions, muzakki and  mustahik. In other words,  the idol society  agency  BAZ is ready  to guarantee and  able to convince muzakki that  his zakat will reach the right. Occasionally can include muzakki in distribution activities, and or provide reporting to muzakki to ensure that the given charity is really used for the need of prosperity mustahik.